2006
DOI: 10.1111/j.1600-6143.2006.01563.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Organ Allograft Tolerance Following Hematopoietic Cell Transplantation

Abstract: Using the miniature swine large animal model we have attempted to determine the relationship between tolerance and the presence of donor cells in the bone marrow, thymus and lineages of peripheral blood in a series of hematopoietic cell transplant recipients receiving delayed donor allografts without immunosuppression. Twenty-two animals receiving hematopoietic cell transplantation and a delayed organ allograft were analyzed. Assays for presence of donor CFUs in bone marrow (by PCR), thymic chimerism (by FACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…When recipient T cells are globally depleted prior to transplant, this central deletion is the major mechanism both inducing and maintaining tolerance, with no meaningful contribution from regulatory mechanisms [10]. Chimerism in thymic DCs was also detected and correlated with tolerance in chimeric non-human primates [11] and swine [12, 13]. In humans, two clinical CKHCT protocols achieved durable chimerism.…”
Section: I) Tolerance Mechanisms Associated With Sustained Mixed Chimmentioning
confidence: 99%
“…When recipient T cells are globally depleted prior to transplant, this central deletion is the major mechanism both inducing and maintaining tolerance, with no meaningful contribution from regulatory mechanisms [10]. Chimerism in thymic DCs was also detected and correlated with tolerance in chimeric non-human primates [11] and swine [12, 13]. In humans, two clinical CKHCT protocols achieved durable chimerism.…”
Section: I) Tolerance Mechanisms Associated With Sustained Mixed Chimmentioning
confidence: 99%
“…By approximating donor-recipient mismatch barriers often seen in clinical transplantations, these animals have been used for large animal studies of cellular and solid organ transplantation. [20][21][22] We now report the isolation and characterization of a porcine analog of human UTCs derived from miniature swine. We also describe the evaluation of immunogenicity of these cells using intravenous and subcutaneous injections across full allogeneic MHC barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow was assayed for the presence of donor colony-forming units (CFUs) by PCR, thymus by both fluorescenceactivated cell sorting (FACS) analysis on thymic cell suspensions and by Southern blots, and peripheral blood by FACS and by in vitro responsiveness to donor MHC. These comparisons showed that engraftment, as indicated by the presence of donor-derived CFU in the bone marrow and detectable thymic chimerism, was the most reliable predictor of subsequent acceptance of a donor-matched renal allograft, whereas peripheral blood chimerism and in vitro assays of responsiveness were less-accurate predictors, although they were also highly correlated with tolerance (Horner et al 2006).…”
Section: Tolerance Through Mixed Chimerismmentioning
confidence: 99%
“…By examining many of the parameters of chimerism detectable in the miniature-swine large-animal model, Horner et al (2006) have attempted to determine which parameters are most indicative of induction of transplantation tolerance by this chimerism. The presence of donor cells in bone marrow, thymus, and various lineages of peripheral blood were examined in a series of 22 HCTrecipients that also received subsequent donor renal allografts without immunosuppression.…”
Section: Tolerance Through Mixed Chimerismmentioning
confidence: 99%